Error and the academic self : the scholarly imagination, medieval to modern - Lerer, Seth, 1955- (Columbia University Press, 2002)
-- ACLA, 3/11/05.
Keywords: English philology -- History.; Great Britain -- Intellectual life.; Scholarly publishing -- Great Britain.; Errors and blunders, Literary -- History.; English literature -- History and criticism -- Theory, etc.; American literature -- History and criticism -- Theory, etc.; Error -- History.; Philologie anglaise -- Histoire.; Grande-Bretagne -- Vie intellectuelle.; Édition savante -- Grande-Bretagne.; Erreurs et bévues littéraires -- Histoire.; Littérature américaine -- Histoire et critique -- Théorie, etc.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- European -- General.; English literature -- Theory, etc.; English philology; Error; Errors and blunders, Literary; Intellectual life; Scholarly publishing; Great Britain; Criticism, interpretation, etc.; History